O turismo na agenda do desenvolvimento local: desafios de uma região paranaense rumo ao destino turístico inteligente - Melo, Edson Santos (2024)
The tourism sector has consolidated itself as a relevant economic activity, largely due to its ability to encourage the generation of employment, income and local development. Furthermore, destinations have been constantly challenged not only to improve their management, but also to incorporate the appropriation of new technologies and innovations. Aware of these changes, many destinations are reconfiguring themselves, aiming to transform the reality of local tourism. Paraná is an example of this, as there is a ten-year plan whose focus is to transform the state, including its 18 tourist regions, into a quality, intelligent and innovative tourist destination. Thus, this study had the general objective of analyzing the strategic alignment of municipalities linked to the Vales do Iguaçu Tourist Region in relation to the transformation of local destinations into smart tourist destinations (DTI). Given the specificity of the theme and the local arrangement, the contributions arising from classical theories of regional development were adopted as a theoretical contribution, with emphasis on the contributions arising from the Theory of Endogenous Development. As a methodological approach, the study was structured based on the mixed method approach. Thus, in the quantitative stage, we sought to analyze the economic importance of tourist activity for the municipalities in the region, using indicators of the regional economy capable of revealing the locational, structural and spatial dynamics of the activity. In the qualitative phase, documentary research was carried out, in addition to the application of forms and interviews, with public managers of the municipalities as participants, in addition to the Regional Governance Instance and the State Secretariat for Tourism. The results demonstrated that, after a period of 10 years, the tourism sector in the region continued to be concentrated in a few municipalities, thus not being noticed any effects of boost, spillover to neighboring municipalities or even linkages between the activities analyzed. There was also a complete misalignment of actions at the municipal level with the plans that guide actions for the DTI. Furthermore, despite local managers expressing knowledge about DTI and even admitting its importance for improving destination management, experience of visitors and quality of life residents, there were limitations in the inclusion of the theme, with only one municipality in the region took the initiative to implement the methodology. Barriers to be overcome were also evident, ranging from disarticulation of local actors, qualification of municipal managers to work in the area, scarcity of financial resources and difficulty in modernizing technological infrastructure. Finally, a difference was observed in the understanding of the DTI issue when comparing the perceptions of municipal managers and the other interviewees. With this, it is understood that there is a primordial need to approach and strengthen the expectations and actions of all actors involved in planning for the tourism sector in the region, this being a possible step towards leveraging the activity and, consequently, making destinations local more attractive and competitive.